2007
DOI: 10.1038/sj.eye.6702888
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection of retinal ganglion cell function and their central nervous system targets

Abstract: Technological advances have enabled the observation of a large number of retinal ganglion cells (RGCs) in an objective manner. In animal models, it has been shown how retinal ischaemia induces profound functional and structural alterations of the inner retinal and RGC layers by 3 months. These findings reflect degeneration of the inner retinal layers, the RGC population and of the retinotectal projection. Functionally, this implies a permanent disconnection of the retina from its main retinorecipient target re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 11 publications
1
12
0
2
Order By: Relevance
“…A transient insult to the retina triggers a protracted degenerative event in the RGC population; for example, 75 minutes of acute elevation of the intraocular pressure induces retinal ischemia and ocular deformation that leads within the first week to the death of approximately 65% of the RGC population, and this is followed by a protracted additional loss of approximately 22% of the RGC population by day 45. Such a time-dependent loss of RGCs is in agreement with previous studies in adult rats in which retrograde labeling 32,[53][54]70 or immunocytochemical 52,55 techniques were employed to identify and count RGCs following transient ischemia of the retina. The effects of AOH on the thickness of the retinal layers were not investigated in the present study, but previous studies following the transient ischemia of the retina induced by selective ligature of the ophthalmic vessels indicate an important decrease in retinal layer thickness with time 71 or even in the overall volume of the superficial layers of the contralateral superior colliculus, which receive the main input from the injured eye.…”
Section: Aoh Induces Progressive Brn3a þ Rgc Losssupporting
confidence: 90%
See 1 more Smart Citation
“…A transient insult to the retina triggers a protracted degenerative event in the RGC population; for example, 75 minutes of acute elevation of the intraocular pressure induces retinal ischemia and ocular deformation that leads within the first week to the death of approximately 65% of the RGC population, and this is followed by a protracted additional loss of approximately 22% of the RGC population by day 45. Such a time-dependent loss of RGCs is in agreement with previous studies in adult rats in which retrograde labeling 32,[53][54]70 or immunocytochemical 52,55 techniques were employed to identify and count RGCs following transient ischemia of the retina. The effects of AOH on the thickness of the retinal layers were not investigated in the present study, but previous studies following the transient ischemia of the retina induced by selective ligature of the ophthalmic vessels indicate an important decrease in retinal layer thickness with time 71 or even in the overall volume of the superficial layers of the contralateral superior colliculus, which receive the main input from the injured eye.…”
Section: Aoh Induces Progressive Brn3a þ Rgc Losssupporting
confidence: 90%
“…30 Retinal injuries may result in RGC loss, which may be prevented with a number of neuroprotective substances. [31][32][33][34][35] Among the RGC neuroprotective agents, the neurotrophin brain derived neurotrophic factor (BDNF) has been shown to be the most efficacious, [36][37][38] but its effects are only transient and thus result in delayed RGC death. [39][40][41][42][43] BDNF has also been shown to be neuroprotective for the general population of RGCs against acute 31,[44][45] or chronic ocular hypertension, 17,[46][47][48][49][50] but not for the population of m þ RGCs.…”
mentioning
confidence: 99%
“…In the experimental mice, there was a marked reduction in the amount of CTB-labeled retinal afferents in the superficial layers of the contralateral SC; there were small patches in which CTB labeling was reduced allowing observation of individual axons and their terminal arborizations. In addition, there were areas with little to none CTB immunoreactivity that often presented the form of a column extending in the dorsoventral axis of the visual layers of the SC, resembling the deployment of rodent axon terminals (Ling et al, 1998) and suggesting degeneration of retinal axons and their terminals, as observed following other types of retinal insults (Avilés-Trigueros et al, 2003;MayorTorroglosa et al, 2005;Vidal-Sanz et al, 2007). The lateral extension of these areas varied from a small narrow column to almost one half or more of the SC mediolateral extension (Fig.…”
Section: Anterograde Effects Of Oht-induced Retinal Degeneration On Tmentioning
confidence: 93%
“…La cuantificación de las CGRs se ha aplicado en roedores a diferentes modelos experimentales de enfermedades de retina, como: isquemia-reperfusión (Sellés-Navarro et al, 1996;Lam et al, 1997;Lafuente et al, 2001Lafuente et al, , 2002Vidal-Sanz et al, 2007), aplastamiento parcial o total del nervio óptico (Yoles et al, 1999;Parrilla-Reverter et al, 2009a, b;Nadal-Nicolas 2009, axotomía de nervio óptico (Vidal-Sanz et al,.1988, Peinado-Ramón et al,. 1996, Nadal-Nicolas et al, .2009, Galindo-Romero et al, 2011, Sánchez-Migallón, et al, 2011, inyección citotóxica (Vorwerk et al, 1996) o elevación crónica de la presión intraocular (Laquis et al, 1988, Sawada y Nevfeld 1999Salinas-Navarro et al, 2009c.…”
Section: Cuantificación De Las Células Ganglionares De La Retinaunclassified
“…Mediante el contaje automático obtenemos el valor exacto de la población total de las CGRs (Danias et al, 2002;Marco-Gomariz et al, 2006;Vidal-sanz et al, 2007;Nadal-Nicolás et al, 2009;Salinas-Navarro et al, 2009a, b;García-Ayuso et al, 2010;Galindo-Romero et al, 2011). El contaje automático es un procedimiento reproducible, rápido y objetivo que permite el análisis de un gran número de retinas, evita la pérdida de información y sesgo en la estimación que se genera por el método de muestreo ya que el área muestreada normalmente es una pequeña porción de la retina (como máximo el 15% del total).…”
Section: Contaje Automáticounclassified